The Role of Macrophage Iron Overload and Ferroptosis in Atherosclerosis - Jiedong Ma; Hongqi Zhang; Yufei Chen; Xiaojin Liu; Jiamin Tian; Wei Shen (Biomolecules, 2022)
Ferroptosis is a new type of cell death caused by iron-dependent lipid peroxidation. In recent years, it has been found that ferroptosis can promote the progression of atherosclerosis (AS). Macrophages have been proven to play multiple roles in the occurrence and development of AS. Iron is a necessary mineral that participates in different functions of macrophages under physiological conditions. But iron overload and ferroptosis in macrophages may promote the progression of AS. Herein, we summarize the role of iron overload and ferroptosis in macrophages in AS from the perspective of iron metabolism, and iron overload and ferroptosis are significant contributors to AS development.